Analisis Pertumbuhan Fintech Sebelum dan Saat Pandemi Covid-19 di Indonesia - Indira Subagia; Kharisya Ayu Effendi (Politeknik Ganesha Medan, 2023)
Fintech in development has fluctuations in every sentiment, both negative and positive and has had an impact on its development. Before the Covid-19 pandemic occurred, many people still use traditional financial services which were carried out through offline payment transactions and carrying cash even though fintech options were available. During the Covid-19 pandemic occurred, financial services changed offline habits into online activities. However, inconsistencies occurred between loan disbursement which increased while the interest trend in fintech financing decreased when the Covid-19 pandemic hit. The purpose of this study is to analyze whether there were differences before and during the Covid-19 pandemic among fintech lenders in Indonesia. analyze whether there were differences before and during the Covid-19 pandemic for fintech borrowers in Indonesia. The data used is transaction data of fintech lenders and borrowers in Indonesia from 2018 – 2022. This study uses the Paired Sample t-Test and the Wilcoxon Test with the Eviews 12 test tool. The results of this study indicate that there are significant differences in lender transactions and borrowers in conditions before the entry of Covid-19 to the time of entry of Covid-19 to Indonesia. The conclusion is that this significant difference is because during Covid-19, especially investors in Indonesia experienced many problems from health to finance, so when Covid-19 occurred they held back money more than investing in fintech so that lender transactions decreased. In borrower transactions due to lender transactions as lenders decreasing so that loan requests by borrowers that can be fulfilled also decrease.